Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ejic.201600112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ligand Halogenation on the Electron Localization, Geometry and Spin State of Low‐Coordinate (β‐Diketiminato)iron Complexes

Abstract: This contribution explores the influences of incorporating electron-withdrawing CF3 and halide groups into β-diketiminate iron complexes of tetrazene and isocyanide. The synthesis of a new halogenated β-diketimine (LCF3,ClH) was accomplished via two different methods, including a novel microwave-assisted synthesis that improves the yield of the difficult condensation. Treatment of an iron(II) complex of this ligand with reductant and azide gives two diiron complexes with novel tetrazenes as bridging ligands. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…From the Mössbauer parameters, we assign the doublet with double integration as Fe I ( δ = 0.66 mm s –1 ; Δ E Q = 2.60 mm s –1 ) and corresponding to Fe2 and Fe3, whereas the parameters of the other doublet are characteristic of high-spin Fe II ( δ = 0.98 mm s –1 ; Δ E Q = 2.15 mm s –1 ) and attributed to Fe1. The δ values assigned to Fe2 and Fe3 are comparable to those for the high-spin (β-diketiminate)-supported iron( i ) complexes with two tert -butylisocyanides 24 or one dinitrogen bound 25 ( c.f. 0.64 or 0.62, respectively), and distinct from the analogous low-spin iron( i ) di- and tri(carbonyl) 26 and tris( tert -butylisocyanide) compounds ( c.f.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…From the Mössbauer parameters, we assign the doublet with double integration as Fe I ( δ = 0.66 mm s –1 ; Δ E Q = 2.60 mm s –1 ) and corresponding to Fe2 and Fe3, whereas the parameters of the other doublet are characteristic of high-spin Fe II ( δ = 0.98 mm s –1 ; Δ E Q = 2.15 mm s –1 ) and attributed to Fe1. The δ values assigned to Fe2 and Fe3 are comparable to those for the high-spin (β-diketiminate)-supported iron( i ) complexes with two tert -butylisocyanides 24 or one dinitrogen bound 25 ( c.f. 0.64 or 0.62, respectively), and distinct from the analogous low-spin iron( i ) di- and tri(carbonyl) 26 and tris( tert -butylisocyanide) compounds ( c.f.…”
Section: Resultsmentioning
confidence: 51%
“…0.12–0.25). 24 This comparison suggests that 2 likely contains high-spin Fe I centers, which is rare for a CO ligated iron center with tris(pyrazolyl)borate Fe I (CO) compounds as the only characterized examples. 16,27 Applying a magnetic field of 2 T at 4.8 K resulted in a slight line broadening for the doublet assigned to Fe( ii ), revealing an internal field of less than 4 T (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48][49][50] Outside of its unprecedented nature in the Fe-S cluster literature, 5 is an uncommon example of a structurally characterized, terminal Fe isocyanide complex with a high-spin ground state. [52][53][54][55][56] To determine if the binding of a single equivalent of t BuNC in 5 is indeed dictated by the steric pressure imposed by the IMes ligands, we carried out halide abstraction from 1 with NaBAr F 4 in the presence of excess t BuNC (Scheme 3B). Although significant amounts of both insoluble materials and 3 were generated, an additional product was observed that is marked by its highly shifted 1 H NMR signals at 17.43 and 9.03 ppm (derived from the backbone CH3 and isopropyl CH3 groups of the I i Pr Me ligands) as well as a new signal at 0.52 ppm (derived from t BuNC ligands).…”
Section: Resultsmentioning
confidence: 99%
“…We tested diethyl ether as a solvent for the crystallization of complexes 1 and 2 , and this resulted in the formation of the monomeric complexes 4 and 5 (Figures and ). Complexes 4 and 5 are relatively rare examples of neutral iron complexes coordinating diethyl ether (approximately a dozen such complexes have been structurally characterized), all of which feature polydentate coligands, except the bis­(diethyl ether) complex of FeCl 3 . 4 and 5 each coordinate a single ether molecule to produce essentially planar coordination of the iron by three oxygen atoms with dissimilar O–Fe–O angles caused by the different ligand sizes. These angles range from 103.62(8) to 146.12(8)° in 4 and from 102.93(4) to 153.86(5)° in 5 , with the widest angles observed between the oxygens of the terminal aryloxide ligands.…”
Section: Resultsmentioning
confidence: 99%